2005
DOI: 10.1079/pns2005418
|View full text |Cite
|
Sign up to set email alerts
|

The effects of conjugated linoleic acid on human health-related outcomes

Abstract: Conjugated linoleic acid (CLA) is a collective term for a mixture of positional and geometric isomers of conjugated dienoic derivatives of linoleic acid. CLA has received considerable attention as a result of animal experiments that report anti-carcinogenic, anti-atherogenic and anti-diabetic properties, and modulation of body composition and immune function. Several studies of CLA supplementation in human subjects have now been published, but in contrast to animal studies there has been marked variation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 71 publications
2
52
0
5
Order By: Relevance
“…Doran@uwe.ac.uk another PUFA, namely conjugated linoleic acids (CLAs). CLA is a group of isomers, which have been demonstrated to enhance immune system, to reduce body weight and to decrease the risk of cancer (Tricon et al, 2005;Bhattacharya et al, 2006). The main natural source of cis-9, trans-11 CLA is meat and milk of ruminants (Song and Kennelly, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Doran@uwe.ac.uk another PUFA, namely conjugated linoleic acids (CLAs). CLA is a group of isomers, which have been demonstrated to enhance immune system, to reduce body weight and to decrease the risk of cancer (Tricon et al, 2005;Bhattacharya et al, 2006). The main natural source of cis-9, trans-11 CLA is meat and milk of ruminants (Song and Kennelly, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is found predominantly in food products from ruminant animals, especially in milk products (Chin et al, 1992). Besides the anticarcinogenic property, CLA also enhances the immune response, increases the feed efficiency and reduces the body fat (Tricon et al, 2005). Recently, it has been reported that each CLA isomer may have a different pharmacological effect.…”
mentioning
confidence: 99%
“…Evidence derived from studies in animal models and clinical trials indicates that CLA could have a number of beneficial effects on human health, including decreasing carcinogenesis and atherosclerosis, controlling body fat gain and enhancing the immune response as well as decreasing inflammation and other adverse effects typically associated with immune enhancement (McLeod et al, 2004;O'Shea et al, 2004;Wang & Jones, 2004;Lee et al, 2005;Tricon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that CLA inhibits the development of colorectal cancer Lampen et al, 2005;Lee et al, 2005; Beppu et al, 2006). Positional and geometric isomers of CLA may have different physiological effects in humans (Tricon et al, 2005). It is therefore important to understand the formation of specific isomers of CLA during LA metabolism in relation to gut health.…”
mentioning
confidence: 99%